Dampak Pencemaran terhadap Kualitas Air DAS Ciliwung Berdasarkan Data ONLIMO - Neni Triana; Maryuni Maryuni; Uci Sulandari (Pusat riset dan Inovasi Nasional, 2026)
The Ciliwung River Basin is a strategic watershed with significant ecological, social, and economic functions, yet it is increasingly threatened by land use change, rapid urbanization, and water pollution, particularly in the Jakarta metropolitan area. This study aims to assess the water quality condition of the Ciliwung River based on real time monitoring data from the ONLIMO system and to examine spatial and temporal variations in water quality status along the middle and downstream segments. A descriptive quantitative approach was applied using secondary data obtained from three ONLIMO monitoring stations, namely Masjid Istiqlal, Pintu Air Manggarai, and Kelapa Dua Srengseng Sawah, during the period of 6–12 May 2025. The analyzed parameters included temperature, dissolved oxygen, Biochemical Oxygen Demand, nitrate, ammonia, and other relevant physicochemical indicators. The results indicate that the water quality of the Ciliwung River generally falls within lightly to moderately polluted categories, with higher pollution levels observed in the middle segment of the river. Critical parameters influencing pollution status include Biochemical Oxygen Demand, nitrate, ammonia, and consistently low dissolved oxygen levels. These findings demonstrate that pollution in the Ciliwung River is persistent and cumulative, highlighting the urgency of integrated watershed management, strengthening real time water quality monitoring, and enhancing cross sector collaboration to support effective pollution control and sustainable river restoration.